2015
DOI: 10.1007/s10973-015-4660-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of copper(II) complexation by fragments of the FBP28 protein using isothermal titration (ITC) and differential scanning calorimetry (DSC)

Abstract: Isothermal titration calorimetry (ITC) was used to study the interactions between copper(II) ions and peptides with sequences taken from the N-terminal loop of the FBP28 protein (formin-binding protein) WW domain: AcLys-Thr-Ala-Asp-Gly-Lys-Thr-NH 2 (D7) and Ac-Tyr-LysThr-Ala-Asn-Gly-Lys-Thr-Tyr-NH 2 (D9 M), respectively. Measurements were taken at 298.15 K in 20 mM 2-(Nmorpholino)ethanesulfonic acid buffer solution at a pH of 6. The stoichiometry, conditional stability constants and thermodynamic parameters (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…The higher positive value of Δ H of formation of metal and proteins can suggest a less covalent interaction character. Our results of Δ H (3.119 kJ mol −1 ) was comparatively higher than their reports (2.18 kJ mol −1 ), suggesting that the ZCPs of F3bIII might bind to zinc by low possibility of covalent bond. The endothermic curve stabilization at the end of titration (Fig.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…The higher positive value of Δ H of formation of metal and proteins can suggest a less covalent interaction character. Our results of Δ H (3.119 kJ mol −1 ) was comparatively higher than their reports (2.18 kJ mol −1 ), suggesting that the ZCPs of F3bIII might bind to zinc by low possibility of covalent bond. The endothermic curve stabilization at the end of titration (Fig.…”
Section: Resultscontrasting
confidence: 94%
“…Several studies have also reported that the enthalpy of interaction between metal ions and proteins is either endothermic or exothermic, including the interaction of zinc and peptides . Meanwhile, our study revealed that the binding of zinc to sea cucumber ZCPs is endothermic, with Δ H = 3.199 kJ mol −1 , which was similar to the binding between copper and the FBP28 protein . In their study, they mentioned that the thermodynamic stability of the complexes strongly depended on the entropy change.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation